by **leesajohnson** » Fri Jul 01, 2016 4:31 am

a+b = 3 ---- (i)

-b + c = 3 -----(ii)

a + 2c =10 ------(iii)

From the equation (i) we get

b = 3 - a

Now put the value of b into the 2nd equation

-(3-a) + c = 3

c = 3 + 3 - a

c = 6-a

Now we will put value of c into 3rd equation

a+ 2(6-a) = 10

a + 12 - 2a = 10

-a=10 -12

-a= -2

a=2

value of a = 2

put the value of "a" into equation 1st equation

2+ b =3

b= 3-2

b= 1

Now we will put the value of b into 2nd equation

-1 + c= 3

c= 3+1

c= 4

We have found out the value of a,b and c now and values are a = 2, b = 1, c = 4